PENINGKATAN KOMPETENSI PENDIDIK ANAK USIA DINI DALAM MEMFASILITASI ANAK DENGAN KEBUTUHAN KHUSUS PADA SATUAN PENDIDIKAN INKLUSI - Patilima, Hamid; Rahayu, Tutin; Zakiyah, Lailatuz; Sugiarsih, Luluk; Gustini, Eti; Ekaningrum, Zulfi’a (Jurnal Abdimas Bina Bangsa, 2024)
The competence of educators in understanding inclusive education is very important, so Community Service (PKM) activities are needed with the theme "Increasing the Competency of Early Childhood Educators in Facilitating Children with Special Needs in Inclusive Education Units" in partnership with the AL-IMAN Islamic Education Foundation which is supported by the Education Office and Culture, Social Services, Teacher Activity Center (PKG), Jombang Driving School Community (Sepajo) Jombang Regency. Data collection methods were obtained by conducting interviews and directly observing the learning process implemented at YPI Al-Iman Jombang as well as holding workshops on inclusive education to determine the competence of educators through pre-tests and post-tests. The implementation of the workshop activities showed a positive response from the participants. The results of the workshop on inclusive education in Community Service (PKM) in Jombang Regency are expected to increase understanding and increase the competency of PAUD educators regarding the scope of children with special needs and appropriate handling in inclusive schools that can be applied in their respective institutions